Mini-implants, mega solutions: a review - Narsingoju, Alaveni Manga; Ravi Kumar, C; Harilal, G; Lukka, Pavani (International Journal of Dental Materials, 2021)
Dental implants have evolved as a standard treatment option for the replacement of missing teeth. Though this treatment modality provides a high level of patient satisfaction and success, it cannot be performed in all cases. Implant use is also restricted when the quality and quantity of bone at the edentulous site is limited, in addition to medically impaired patients. Among the conditions are remaining ridges with reduced interdental spacing, atrophic edentulous maxillary and mandibular ridges, and narrow ridges such as the mandibular incisor and maxillary lateral incisor area. A proper augmentation method for the placement of a regular diameter implant (3.75 to 7 mm) can improve the height and width of bone at such sites. However, bone augmentation and bone grafting procedures are rarely undertaken due to financial constraints, the risk of subjecting the patient to additional surgical procedures, the added time factor, or the guarded prognosis of the grafted site. In such cases, mini-implants are the choice of treatment. Mini-implants have the potential to be a viable alternative to standard-diameter implants in some circumstances. Benefits of mini-implants can be gained by replacing a single missing tooth, or preferably they must be used in multiples to retain fixed dental prostheses and might serve as an inexpensive, and efficient solution for retaining overdentures in selected cases.